La tradizione fulgurale antica e medievale con la riedizione di un testimone della ceraunoscopia greca (P.Oxy. VI 885) - Costanza, Salvatore; Papathomas, Amphilochios (Chronique d’Égypte, 2024)
Abstract Examine in detail the ancient and medieval tradition of ceraunoscopy, that is, the divinatory interpretation of lightning. Furthermore, it offers a new edition of with commentary on P.Oxy. VI 885, an important papyrological testimony to ceraunoscopy.